Hepatic macrophage niche: a bridge between HBV-mediated metabolic changes with intrahepatic inflammation - Wang, Jun; Lu, Hongzhou; Li, Qian (Frontiers in Immunology, 2024)
Hepatitis B Virus (HBV) is a stealthy and insidious pathogen capable of inducing chronic necro-inflammatory liver disease and hepatocellular carcinoma (HCC), resulting in over 1.1 million deaths worldwide. The traditional understanding of Chronic Hepatitis B (CHB) progression has focused on the complex interplay among ongoing virus replication, aberrant immune responses, and liver pathogenesis. However, the dynamic progression and crucial factors involved in the transition from HBV infection to immune activation and intrahepatic inflammation remain elusive. Recent insights have illuminated HBV's exploitation of the sodium taurocholate cotransporting polypeptide (NTCP) and manipulation of the cholesterol transport system shared between macrophages and hepatocytes for viral entry. These discoveries deepen our understanding of HBV as a virus that hijacks hepatocyte metabolism. Moreover, hepatic niche macrophages exhibit significant phenotypic and functional diversity, zonal characteristics, and play essential roles, either in maintaining liver homeostasis or contributing to the pathogenesis of chronic liver diseases. Therefore, we underscore recent revelations concerning the importance of hepatic niche macrophages in the context of viral hepatitis. This review particularly emphasizes the significant role of HBV-induced metabolic changes in hepatic macrophages as a key factor in the transition from viral infection to immune activation, ultimately culminating in liver inflammation. These metabolic alterations in hepatic macrophages offer promising targets for therapeutic interventions and serve as valuable early warning indicators, shedding light on the disease progression.